Non-culpable ignorance and HIV criminalisation - Flanigan, Jessica (Journal of medical ethics, 2014)
In this essay, I argue that any legal framework that addresses sexual transmission of HIV should be sensitive to the way that culpability can be mitigated by moral and factual ignorance. Though it is wrong to transmit HIV, public officials should be wary of criminalising transmission because people with HIV may be excused if they suffer from blameless moral or factual ignorance. I begin with the widely shared premise that blameless ignorance about one's HIV status is an excuse for sexual transmission of infections. I then extend this premise to other kinds of non-moral ignorance about HIV. Next, I argue that blameless moral ignorance also excuses transmission of HIV. There is some evidence of significant blameless non-moral and moral ignorance about HIV transmission. In these cases, transmission is excused. In light of the presence of moral and non-moral ignorance about HIV, I conclude that public health officials should encourage moral deliberation about HIV transmission and also that criminal penalties for HIV transmission are unwarranted even in some cases of knowing or intentional transmission.